Carbon source composition for lithium iron phosphate precursor slurry, lithium iron phosphate precursor slurry and application of lithium iron phosphate precursor slurry
By designing a carbon source composition with a nitrogen doped function, for the front drives of the lithium iron phosphate, the problem of low carbon source in existing technologies and poor effects of dispersion agent have been solved, and the performance of lithium iron phosphate batteries is improved. The production efficiency of battery materials.
Patent Information
- Application Number
- CN202411544280.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, lithium iron phosphate batteries are prone to electrochemical deactivation in a high-rate discharge state, and the carbon source quality is low and the dispersant effect is poor, which affects the performance of the battery.
Design a carbon source composition for lithium iron phosphate, including amino acid polymers and amino acids. It has nitrogen doping function and good decentralization capabilities, which can reduce the viscosity of the lithium iron phosphate before.
Improve the decentralized effect and carbon covering quality of the lithium iron phosphate, enhance the compact density and conductivity of the lithium iron phosphate, and improve the first charge capacity of the battery and the charging and discharge performance.
Smart Images

Figure BDA0005113419750000111 
Figure BDA0005113419750000121
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a carbon source composition for lithium iron phosphate precursor slurry, the lithium iron phosphate precursor slurry and applications thereof. Background Art
[0002] Lithium iron phosphate has the characteristics of high energy density, long cycle life and high safety, and has received widespread attention in the fields of electric vehicles and energy storage. However, lithium iron phosphate batteries are particularly prone to electrochemical deactivation under high-rate discharge conditions, which affects their application in electric vehicles and other fields. Therefore, the performance improvement of lithium iron phosphate batteries has become the focus of many researchers.
[0003] The mixing and dispersion process of lithium iron phosphate precursor is an important link in the production of lithium batteries. The dispersion and carbon source quality directly affect the performance of the sintered material. During the processing of lithium iron phosphate precursor, the viscosity of the electrode active material in the slurry will gradually increase during the grinding process, affecting production efficiency and causing problems such as filter clogging. In addition, the agglomeration of lithium iron phosphate precursor particles and the difference in the uniformity of carbon source coating will affect the subsequent sintering quality.
[0004] CN103682363A discloses a method for preparing a lithium iron phosphate battery material using a novel mixed dispersant, wherein the novel mixed dispersant is one or more of zinc oxide, magnesium oxide, distilled water, and ethylenediamine inorganic solvents; CN104300119A discloses a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps: mixing iron phosphate, a lithium source, a carbon source, a dispersant, a binder, and water, stirring, grinding, and granulating to obtain a lithium iron phosphate precursor, and the lithium iron phosphate precursor is roasted in a protective gas atmosphere, and cooled to obtain a lithium iron phosphate positive electrode material. In the process of preparing lithium iron phosphate, the quality of the carbon source used in the prior art is relatively low, and the existing dispersant has a poor dispersing effect on the lithium iron phosphate precursor. With the demand for lithium battery production and the advancement of material technology, it is necessary to further improve the dispersing effect and carbon source quality of the lithium iron phosphate precursor.
[0005] Non-metallic element doping is an effective means to improve the performance of lithium iron phosphate batteries, which can improve the reversibility, rate performance and cycle life of the battery. Appropriate doping with nitrogen, sulfur, fluorine and other elements can provide more possibilities for the application of lithium iron phosphate batteries. Therefore, it is urgent to design a high-quality carbon source with nitrogen doping function and dispersion performance, and can reduce the viscosity of lithium iron phosphate precursor slurry, so as to meet the high quality requirements of carbon source for preparing electrode materials, especially preparing lithium iron phosphate positive electrode materials. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a carbon source composition for lithium iron phosphate precursor slurry, lithium iron phosphate precursor slurry and applications thereof. Through the screening and design of components, the carbon source composition provided by the present invention not only has good dispersibility for lithium iron phosphate precursor, but also has the effect of reducing the viscosity of the lithium iron phosphate precursor slurry during the processing of the lithium iron phosphate precursor, and also has nitrogen doping function and high quality; the carbon-coated lithium iron phosphate prepared by using the carbon source composition provided by the present invention has good compaction density and conductivity.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include a combination of an amino acid polymer and an amino acid; the structural formula of the amino acid contains a C6-C19 aromatic ring and / or a C3-C9 nitrogen heterocycle.
[0009] The present invention starts from the dispersion principle in the lithium iron phosphate processing process, the influencing factors of the carbon coating quality difference, etc., and combines the characteristics of the lithium iron phosphate processing technology to design a carbon source composition suitable for the dispersion and sintering of lithium iron phosphate precursors. The carbon source composition has a nitrogen doping function and can reduce the viscosity of the slurry in the lithium iron phosphate precursor processing process, improve the production efficiency of the carbon-coated lithium iron phosphate, and improve the quality of the carbon layer on the surface of the carbon-coated lithium iron phosphate, thereby improving the compaction density, conductivity and first-charge capacity of the carbon-coated lithium iron phosphate; the compaction density of the carbon-coated lithium iron phosphate is an important indicator, which affects the energy density of the initial battery product. Improving the compaction density can improve the product quality; the carbon-coated lithium iron phosphate prepared using the carbon source composition provided by the present invention has improved conductivity and reduced resistivity, and can improve the charge and discharge performance and first-charge capacity of the battery.
[0010] In the carbon source composition provided by the present invention, the amino acid polymer is mainly used as a carbon source and can provide a nitrogen-doped carbon source coating structure. At the same time, due to its strong adsorption to iron phosphate, it can form a coating on the ground and crushed lithium iron phosphate precursor particles to avoid secondary collision and aggregation, thereby having the function of a dispersant; in the carbon source composition, the amino acid is used as an auxiliary nucleating agent, and its structural formula contains aromatic rings and / or nitrogen heterocycles. In the later process of decomposition and carbonization of the carbon source composition, it can provide nucleation points for carbon source growth, which is conducive to the stable formation of the nitrogen-doped carbon source structure. If this component is not added, the nitrogen doping efficiency will be reduced, affecting the conductivity of the carbon-coated lithium iron phosphate and the first charge capacity of the battery cell.
[0011] In the present invention, the term "amino acid polymer" refers to a class of polymers formed by connecting natural amino acid monomers or their derivatives through amide bonds.
[0012] In the present invention, the C6-C19 may be C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, etc.
[0013] The C3-C9 can be C4, C5, C6, C7, C8, etc.
[0014] In the present invention, the C6-C19 aromatic ring can be a monocyclic aromatic ring or a condensed aromatic ring. The monocyclic aromatic ring means that the group contains at least one benzene ring. When it contains at least two benzene rings, the benzene rings are connected by a single bond. Examples thereof include but are not limited to: a benzene ring, a biphenyl ring, etc.; the condensed aromatic ring means that the group contains at least two aromatic rings, and the aromatic rings share two adjacent carbon atoms and are fused to each other. Examples thereof include but are not limited to: a naphthyl group, anthracenyl group, etc.
[0015] In the present invention, the C3-C9 nitrogen heterocycle can be a monocyclic nitrogen heterocycle or a condensed nitrogen heterocycle, and the condensed nitrogen heterocycle includes a benzene condensed heterocycle (a benzene ring is condensed with a nitrogen heterocycle) or a hetero condensed heterocycle (a nitrogen heterocycle is condensed with a nitrogen heterocycle), illustratively including but not limited to: a pyrrole ring, a pyrazole ring, an imidazole ring, a pyridine ring, a pyrimidine ring, a purine ring, an indole ring, etc.
[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] As a preferred technical solution, the amino acid polymer includes any one of polyaspartic acid, polytryptophan, polyhistidine, polytyrosine or polyproline, or a combination of at least two of them.
[0018] Preferably, the molecular weight of the amino acid polymer is 3-8 kDa, for example, 3.2 kDa, 3.4 kDa, 3.6 kDa, 3.8 kDa, 4 kDa, 4.2 kDa, 4.4 kDa, 4.6 kDa, 4.8 kDa, 5 kDa, 5.5 kDa, 6 kDa, 6.5 kDa, 7 kDa, 7.5 kDa, 8 kDa, etc.
[0019] Preferably, the decomposition temperature of the amino acid is 270-340°C, for example, it may be 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, etc.
[0020] Preferably, the amino acids include histidine and / or tryptophan.
[0021] Preferably, the mass ratio of the amino acid polymer to the amino acid is (10-40):1, for example, it can be 12:1, 14:1, 16:1, 18:1, 20:1, 22:1, 24:1, 26:1, 28:1, 30:1, 32:1, 34:1, 36:1, 38:1, etc.
[0022] Preferably, the components of the carbon source composition further include an auxiliary carbon source, and the auxiliary carbon source includes any one of glucose, sucrose, polyethylene glycol or starch, or a combination of at least two thereof.
[0023] In the present invention, the auxiliary carbon source can be used to assist in coating the carbon layer on the surface of lithium iron phosphate and to adjust the nitrogen doping ratio.
[0024] Preferably, the mass ratio of the amino acid polymer to the auxiliary carbon source is (0.5-5.5):1, for example, it can be 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.2:1, 5.4:1, etc.
[0025] Preferably, the components of the carbon source composition further include a polyacid.
[0026] Preferably, the polyacid includes any one of oxalic acid, 1,3-malonic acid, 1,4-succinic acid, citric acid, malic acid or isopentanedioic acid, or a combination of at least two thereof.
[0027] In the present invention, the polyacid can form a carboxyl coating layer on the surface of the lithium iron phosphate precursor, promote the dispersion of the lithium iron phosphate precursor through electrostatic repulsion, and has an auxiliary dispersion effect. If this component is not added, the viscosity of the lithium iron phosphate precursor slurry will be high.
[0028] Preferably, the mass ratio of the amino acid polymer to the polyacid is (4-11):1, for example, it can be 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, etc.
[0029] Preferably, the components of the carbon source composition also include water.
[0030] Preferably, the mass percentage of water in the carbon source composition is 20-50%, for example, it can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50% and the like.
[0031] The present invention does not impose any particular limitation on the method for preparing the carbon source composition provided, as long as a uniformly mixed carbon source composition can be obtained.
[0032] In a second aspect, the present invention provides a lithium iron phosphate precursor slurry, wherein raw materials for preparing the lithium iron phosphate precursor slurry include a phosphorus source, an iron source, a lithium source, a carbon source composition as described in the first aspect, and a combination of water.
[0033] Preferably, the phosphorus source comprises ferric orthophosphate.
[0034] Preferably, the iron source comprises ferric orthophosphate.
[0035] Preferably, the lithium source comprises lithium carbonate.
[0036] Preferably, the mass ratio of the lithium source to the carbon source composition is (0.5-1.5):1, for example, it can be 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.45:1, etc.
[0037] Preferably, the solid content of the lithium iron phosphate precursor slurry is 40-70%, for example, it can be 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, etc.
[0038] In a third aspect, the present invention provides a method for preparing the lithium iron phosphate precursor slurry as described in the second aspect, the preparation method comprising: mixing a phosphorus source, an iron source, a lithium source, the carbon source composition as described in the first aspect, and water to obtain the lithium iron phosphate precursor slurry.
[0039] Preferably, the mixing further comprises a grinding step.
[0040] Preferably, the grinding time is 30-60 min, for example, it can be 32 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min, etc.
[0041] Preferably, the grinding rotation speed is 1000-2000 rpm, for example, it can be 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, etc.
[0042] Preferably, the grinding is carried out in the presence of zirconium beads.
[0043] In a fourth aspect, the present invention provides a carbon-coated lithium iron phosphate, wherein the carbon-coated lithium iron phosphate is obtained by sequentially drying and sintering the lithium iron phosphate precursor slurry as described in the second aspect.
[0044] Preferably, the drying method comprises spray drying.
[0045] Preferably, the spray drying is carried out under the conditions of an inlet temperature of 200-250°C (e.g., 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, etc.) and an outlet temperature of <100°C (e.g., 99°C, 98°C, 96°C, 94°C, 90°C, 85°C, 80°C, 75°C, 70°C, 60°C or 50°C, etc.).
[0046] Preferably, the sintering temperature is 600-800°C, for example, it may be 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, etc.
[0047] Preferably, the sintering time is 4-7 h, for example, it can be 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h, 6 h, 6.2 h, 6.4 h, 6.6 h, 6.8 h, etc.
[0048] Preferably, the step of crushing is further included after the sintering is completed.
[0049] In a fifth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the carbon-coated lithium iron phosphate as described in the fourth aspect.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The carbon source composition provided by the present invention has a good dispersing effect on the lithium iron phosphate precursor and can reduce the viscosity of the lithium iron phosphate precursor slurry, and its viscosity is 76-107 mPa·s;
[0052] (2) The carbon source composition provided by the present invention is of high quality. The carbon-coated lithium iron phosphate prepared by using the carbon source composition provided by the present invention has a high compaction density and a low resistivity. The compaction density is 2.46-2.56 g / cm 3 , the resistivity is 11.91-17.66Ω·cm. DETAILED DESCRIPTION
[0053] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] The sources of some components in the embodiments and comparative examples are as follows:
[0055] (1) Polyaspartic acid: purchased from Wuhan Proloff Biotechnology Co., Ltd., with a content of 99%, a molecular weight of 5.75 kDa, CAS: 35608-40-6;
[0056] (2) Histidine: purchased from Sinopharm Chemical Reagent Co., Ltd., with a decomposition temperature of 277°C;
[0057] (3) Tryptophan: purchased from Sinopharm Chemical Reagent Co., Ltd., with a decomposition temperature of 290°C;
[0058] (4) Oxalic acid: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0059] (5) Citric acid: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0060] (6) Glucose: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0061] (7) Sucrose: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0062] (8) Polyethylene glycol: purchased from Sinopharm Chemical Reagent Co., Ltd., PEG6000;
[0063] (9) Glycine: purchased from Sinopharm Chemical Reagent Co., Ltd., with a decomposition temperature of 236 °C.
[0064] Example 1
[0065] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include 22 parts by weight of polyaspartic acid, 1 part by weight of tryptophan, 22 parts by weight of polyethylene glycol, 5 parts by weight of citric acid and 50 parts by weight of water.
[0066] Example 2
[0067] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include, by weight, 38 parts by weight of polyaspartic acid, 1 part by weight of tryptophan, 7.5 parts by weight of sucrose, 3.5 parts by weight of citric acid and 50 parts by weight of water.
[0068] Example 3
[0069] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include, by weight, 15 parts by weight of polyaspartic acid, 1.5 parts by weight of histidine, 30 parts by weight of glucose, 3.5 parts by weight of oxalic acid and 50 parts by weight of water.
[0070] Example 4
[0071] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include, by weight, 22.3 parts by weight of polyaspartic acid, 0.3 parts by weight of tryptophan, 22.3 parts by weight of polyethylene glycol, 5.1 parts by weight of citric acid and 50 parts by weight of water.
[0072] Example 5
[0073] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include, by weight, 21.1 parts by weight of polyaspartic acid, 3 parts by weight of tryptophan, 21.1 parts by weight of polyethylene glycol, 4.8 parts by weight of citric acid and 50 parts by weight of water.
[0074] Example 6
[0075] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include 39.3 parts by weight of polyaspartic acid, 1.8 parts by weight of tryptophan, 8.9 parts by weight of citric acid and 50 parts by weight of water.
[0076] Example 7
[0077] A carbon source composition for lithium iron phosphate precursor slurry comprises, in parts by weight, 24.5 parts by weight of polyaspartic acid, 1 part by weight of tryptophan, 24.5 parts by weight of polyethylene glycol and 50 parts by weight of water.
[0078] Comparative Example 1
[0079] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include 22.4 parts by weight of polyaspartic acid, 22.4 parts by weight of polyethylene glycol, 5.2 parts by weight of citric acid and 50 parts by weight of water.
[0080] Comparative Example 2
[0081] A carbon source composition for lithium iron phosphate precursor slurry, wherein the components of the carbon source composition include, by weight, 1.8 parts by weight of tryptophan, 39.3 parts by weight of polyethylene glycol, 8.9 parts by weight of citric acid and 50 parts by weight of water.
[0082] Comparative Example 3
[0083] A carbon source composition for lithium iron phosphate precursor slurry, which differs from Example 1 only in that tryptophan is replaced by glycine, and the remaining components and amounts are the same as those in Example 1.
[0084] The sources of some components in the following application examples and comparative application examples are as follows:
[0085] (1) Ferric orthophosphate: analytical grade reagent purchased from Sinopharm Chemical Reagent Co., Ltd.
[0086] (2) Lithium carbonate: analytical grade reagent purchased from Sinopharm Chemical Reagent Co., Ltd.
[0087] Application Example 1
[0088] A carbon-coated lithium iron phosphate and a preparation method thereof, the preparation method comprising the following steps:
[0089] (1) 40.12 parts by weight of ferric orthophosphate, 10.03 parts by weight of lithium carbonate, 11.68 parts by weight of the carbon source composition provided in Example 1, and 38.17 parts by weight of water were added to a high-density polyethylene stirring cup, mixed evenly to obtain a mixed slurry, and then mixed with zirconium beads, the mass of the zirconium beads being 50% of the mass of the mixed slurry, and grinding at a speed of 1000 rpm for 30 minutes using a centrifugal degassing machine to simulate a sand mill to obtain a lithium iron phosphate precursor slurry;
[0090] (2) The lithium iron phosphate precursor slurry is spray-dried at an inlet temperature of 200-250° C. and an outlet temperature of <100° C., then sintered at 735° C. for 4 h, and finally crushed to obtain the carbon-coated lithium iron phosphate.
[0091] Application Example 2-7
[0092] A carbon-coated lithium iron phosphate and a preparation method thereof, which differs from Application Example 1 only in that the carbon source composition provided in Example 1 in step (1) is replaced by the carbon source composition provided in Examples 2-7 in equal mass, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.
[0093] Comparative application example 1
[0094] A carbon-coated lithium iron phosphate and a preparation method thereof, which differs from Application Example 1 only in that the mass of the carbon source composition provided in Example 1 in step (1) is replaced by glucose, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.
[0095] Comparative Application Example 2-4
[0096] A carbon-coated lithium iron phosphate and a preparation method thereof, which differs from Application Example 1 only in that the carbon source composition provided in Example 1 in step (1) is replaced by the carbon source composition provided in Comparative Examples 1-3 in equal mass, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.
[0097] Performance Testing
[0098] (1) Viscosity: Referring to GB / T10247-2008, the viscosity of the lithium iron phosphate precursor slurry in the above application examples and comparative application examples was tested using a Brookfield rotary viscometer at a temperature of 25° C., a No. 4 rotor, and a rotation speed of 15-30 rpm;
[0099] (2) Compacted density: Referring to the method for testing the compacted density of powder by the pressure relief method provided in GB / T 24533-2019, the carbon-coated lithium iron phosphate was tested using a PRCD3100 compaction density instrument (IEST-Yuan Neng Technology). 1.0000g of sample was accurately weighed, and a pressure range of 10-200MPa was applied. The pressure interval was 10MPa, and the pressure was maintained for 10s. The pressure was released to 3MPa and the pressure was maintained for 10s. The instrument measured the volume after compaction, and the compacted density of the carbon-coated lithium iron phosphate was calculated.
[0100] (3) Resistivity: Referring to the measurement principle (Principle 4.3) provided in GB / T 40007-2021, the resistivity of carbon-coated lithium iron phosphate was tested using the PRCD3100 compaction density meter (IEST-Yuan Neng Technology). The compacted sample with tested compaction density was used to set the test parameters on the MRMS software. The single-point test mode was selected, the pressure was selected to be 5 MPa, and the pressure was maintained for 15 seconds. Six data were collected for each test sample, and the software automatically read the thickness and resistance and calculated the resistivity data.
[0101] The lithium iron phosphate precursor slurry and carbon-coated lithium iron phosphate provided in the above application examples and comparative application examples were tested according to the above method, and the test results are shown in Table 1:
[0102] Table 1
[0103]
[0104]
[0105] From the comparison between Application Example 1 and Comparative Application Example 1, it can be seen that when glucose is used as the carbon source, the viscosity of the lithium iron phosphate precursor slurry is too high and cannot meet the process requirements of grinding and spray drying; compared with glucose, using the carbon source composition provided by the present invention as the carbon source can greatly reduce the viscosity of the lithium iron phosphate precursor slurry. Even if the solid content of the lithium iron phosphate precursor slurry is increased to 56%, the viscosity of the lithium iron phosphate precursor slurry is still less than 200 mPa·s.
[0106] From the comparison between Application Example 1 and Comparative Application Example 3, it can be seen that when the amino acid polymer in the carbon source composition is removed, the viscosity of the lithium iron phosphate precursor slurry is greatly increased. However, compared with the lithium iron phosphate precursor slurry using glucose as the carbon source (Comparative Application Example 1), due to the auxiliary dispersion effect of the polyacid, the viscosity of the lithium iron phosphate precursor slurry is still reduced to a certain extent.
[0107] The carbon-coated lithium iron phosphate provided in Comparative Application Example 1 uses glucose as the carbon source, and the compaction density is 2.39 g / cm 3 The amino acid polymer in the carbon source composition provided by the present invention effectively reduces the viscosity of the lithium iron phosphate precursor slurry, improves the dispersion effect, improves the coating efficiency of the carbon source layer material on the surface of the lithium iron phosphate, and correspondingly improves the compaction density of the carbon-coated lithium iron phosphate, which can be increased to 2.56 g / cm 3 .
[0108] Compared with comparative application example 1, the conductivity of the carbon-coated lithium iron phosphate prepared by using the carbon source composition provided by the present invention as a carbon source is significantly improved. The conductivity of the carbon-coated lithium iron phosphate provided by application example 1, application example 5 (using a carbon source composition with a high amino acid content), application example 6 (using a carbon source composition without an auxiliary carbon source) and application example 7 (using a carbon source composition without a polyacid) is not much different, indicating that the amino acid polymer in the carbon source composition provided by the present invention plays a leading role in reducing the resistivity of the carbon-coated lithium iron phosphate.
[0109] From the comparison between Application Example 1 and Application Example 4, it can be seen that the content of amino acids in the carbon source composition is too low, and the conductivity of the carbon-coated lithium iron phosphate deteriorates; from the comparison between Application Example 1, Comparative Application Example 1, Comparative Application Example 2 and Comparative Application Example 4, it can be seen that if the amino acids are removed or inappropriate amino acids are selected, the conductivity of the carbon-coated lithium iron phosphate deteriorates significantly, but the conductivity is better than that of the carbon-coated lithium iron phosphate using glucose alone as the carbon source, indicating that nitrogen-doped carbon sources can reduce resistivity.
[0110] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the carbon source composition for lithium iron phosphate precursor slurry, lithium iron phosphate precursor slurry and its application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A carbon source composition for lithium iron phosphate precursor slurry, characterized in that: The components of the carbon source composition include a combination of amino acid polymers and amino acids; The structural formula of the amino acid contains a C6-C19 aromatic ring and / or a C3-C9 nitrogen heterocyclic ring.
2. The carbon source composition according to claim 1, characterized in that The amino acid polymer includes any one of polyaspartic acid, polytryptophan, polyhistidine, polytyrosine or polyproline, or a combination of at least two thereof; Preferably, the molecular weight of the amino acid polymer is 3-8 kDa; Preferably, the decomposition temperature of the amino acid is 270-340°C; Preferably, the amino acids include histidine and / or tryptophan; Preferably, the mass ratio of the amino acid polymer to the amino acid is (10-40):
1.
3. The carbon source composition according to claim 1 or 2, characterized in that The components of the carbon source composition also include an auxiliary carbon source, and the auxiliary carbon source includes any one or a combination of at least two of glucose, sucrose, polyethylene glycol or starch; Preferably, the mass ratio of the amino acid polymer to the auxiliary carbon source is (0.5-5.5):
1.
4. The carbon source composition according to any one of claims 1 to 3, characterized in that The components of the carbon source composition also include polyacids; Preferably, the polyacid comprises any one or a combination of at least two of oxalic acid, 1,3-malonic acid, 1,4-succinic acid, citric acid, malic acid or isopentanedioic acid; Preferably, the mass ratio of the amino acid polymer to the polyacid is (4-11):
1.
5. The carbon source composition according to any one of claims 1 to 4, characterized in that The components of the carbon source composition also include water; Preferably, the mass percentage of water in the carbon source composition is 20-50%.
6. A lithium iron phosphate precursor slurry, characterized in that: The raw materials for preparing the lithium iron phosphate precursor slurry include a phosphorus source, an iron source, a lithium source, a carbon source composition as described in any one of claims 1 to 5, and a combination of water.
7. The lithium iron phosphate precursor slurry according to claim 6, characterized in that: The phosphorus source includes ferric orthophosphate; Preferably, the iron source comprises ferric orthophosphate; Preferably, the lithium source comprises lithium carbonate; Preferably, the mass ratio of the lithium source to the carbon source composition is (0.5-1.5):1; Preferably, the solid content of the lithium iron phosphate precursor slurry is 40-70%.
8. A method for preparing a lithium iron phosphate precursor slurry as claimed in claim 6 or 7, characterized in that: The preparation method comprises: mixing a phosphorus source, an iron source, a lithium source, the carbon source composition according to any one of claims 1 to 5, and water to obtain the lithium iron phosphate precursor slurry; Preferably, after the mixing is completed, a grinding step is also included; Preferably, the grinding time is 30-60 min; Preferably, the grinding speed is 1000-2000 rpm.
9. A carbon-coated lithium iron phosphate, characterized in that: The carbon-coated lithium iron phosphate is obtained by sequentially drying and sintering the lithium iron phosphate precursor slurry as claimed in claim 6 or 7; Preferably, the drying method comprises spray drying; Preferably, the spray drying is carried out under the conditions of an inlet temperature of 200-250°C and an outlet temperature of <100°C; Preferably, the sintering temperature is 600-800°C; Preferably, the sintering time is 4-7h; Preferably, the step of crushing is further included after the sintering is completed.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the carbon-coated lithium iron phosphate as claimed in claim 9.
Citation Information
Patent Citations
Method for using novel material mixing dispersing agents for preparing lithium iron phosphate battery materials
CN103682363A
Preparation method for lithium iron phosphate cathode material
CN104300119A